Working Through Barriers Host Country Institutions and Immigrant Labour Market Performance in Europe - Kogan, Irena; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Working through Barriers deals with the role host countries$1 (Binstitutional characteristics play in the labour market integration of immigrants in the European Union. Drawing on existing research it develops a comprehensive conceptual framework of factors (and underlying mechanisms) affecting immigrant structural integration in the European Union-15. It maps the European countries with respect to three institutional aspects central to immigrant integration, immigration policies, labour market structure and welfare regimes. Further, it presents a descriptive picture of the labour market situation of the immigrant population in the European Union and seeks to explain the variation in labour market outcomes, namely unemployment risk and occupational status, with reference to differences in the characteristics of the immigrant populations on the one hand, and by differences in labour market structure, immigration policies and welfare regimes in European Union countries, on the other. In-depth analyses of a selected number of EU countries are carried out, with the aim of investigating the extent to which immigrants have succeeded or failed in different institutional contexts.s
Immigrant labour market performance: A European perspective -- Explaining Immigrant Labour Market Inequality -- Immigration Policies and Immigrant Selectivity in Europe -- Immigrants and the labour market -- Welfare Regimes and Immigrants$1 (BEmployment Prospects -- Empirical Assessment of the Role of Institutions in the Labour Market Outcomes of Male Immigrants in Fourteen European Union Countries -- Employment Careers and Unemployment Dynamics of Male Immigrants in Germany and Great Britain -- Ex-Yugoslavs in the Austrian and Swedish labour markets131 -- Conclusions.s
Keywords: Social sciences; Statistics; Labor economics; Sociology; Emigration and immigration; Demography; Human geography; Social Sciences; Demography; Labor Economics; Migration; Sociology, general; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Human Geography; Electronic books